How does the S-locus determining self-incompatibility in stone fruits work in self-compatible peach? - Hegedűs, Attila; Halász, Júlia; Szabó, Zoltán; Nyéki, József; Pedryc, Andrzej (Acta Agraria Debreceniensis, 2005)
The majority of stone fruit species are self-incompatible, a feature that is determined by a specific recognition mechanism between the S-ribonuclease enzymes residing in the pistils and the F-box proteins expressed in the pollen tubes. Failure in the function of any component of this bipartite system resulted in self-compatibility (SC) in many cultivars of Prunus species. Peach (Prunus persica (L.) Batsch.) is the only species in the Prunoideae subfamily that is traditionally known to be self-compatible, but its molecular background is completely unknown. Isoelectric focusing and S-gene specific PCR revealed that SC is not due to functional inability of pistil ribonucleases. We hypothesize that SC may be a consequence of a kind of pollen-part mutation or the action of one or more currently unknown modifier gene(s). Only two S-alleles were identified in a set of peach genotypes of various origin and phenotypes in contrast to the 17–30 alleles described in self-incompatible fruit trees. Most important commercial cultivars carry the same S-allele and are in a homozygote state. This indicates the common origin of these cultivars and also the consequence of self-fertilization. According to the available information, this is the first report to elucidate the role of S-locus in the fertilization process of peach.